2021 trade finance gaps, growth, and jobs survey. - Kim, Kijin; Beck, Steven; Latoja, Ma. Concepcion; Tayag, Mara Claire; Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This will be exacerbated by sharp increases in food and energy prices eating into what country and counterparty limits exist to support trade. The gap will inhibit economic growth and job creation, making economic recovery from the pandemic more difficult. The survey estimates that the gap has hit small companies and those owned by women the hardest, identifies why the gap exists, and suggests what needs to be done to fix it. On its seventh cycle, the 2021 survey respondents included 79 banks from 43 countries and 469 firms from 72 countries from all regions of the world.
Keywords: Public-private sector cooperation -- Asia -- Finance; Industry and state; Information technology; Small business; Electronic book